Pemberian Kasgot Black Soldier Fly Dan PGPR Akar Bambu Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah ( Alium ascalonicum L.) Varietas Tajuk: indonesia - Husain, Indriati; Rahim, Yunnita; Rahman Yusuf, Abd (Jurnal Penelitian Pertanian Terapan, 2024)
The aim of this study was to determine the effect, interaction, and the best dosage and concentration of Black Soldier Fly (BSF) Kasgot and Plant Growth Promoting Rhizobacteria (PGPR) bamboo roots an the growth and yield of shallot (Allium ascalonicum L.) of canopy varities. This study was conducted from February to June 2023 at SMK PPN Gorontalo, Telaga Sub District, Gorontalo Regency, Furthermore, this studi used a factorial randomized block design (RDB) with 2 factors. The first factor was Black Soldie Fly Kasgot (K) with 4 levels: K0 = control, K1 = 200 g/polybag, K2 = 300 g/polybag, K3 = 400 g/polybag. Meanwhile, the second factor was PGPR of bamboo roots (P) with 4 levels: P0 = (control), P1 = 20 ml/litre of water, P2 = 30 ml/litre of water, P3 = 40 ml/litre of water. The parameters measured were plant height, number of leaves, number of tillers, fresh tuber weight, tuber number, tuber diameter and dry tuber weight. The observational data were then analyzed using analysis of variance (ANOVA α = 5%) and continued with the DMRT test with a level of 5%. The results showed that the application of Black Soldier Fly (BSF) Kasgot had a significant effect on plant height, number of leaves, number of tillers, fresh tuber weight, tuber number, tuber diameter and dry tuber weight of shallot plants. Meanwhile, the PGPR of bamboo roots had a significant effect on plant height and number of leaves. There was an interaction between the two treatments on the parameters of plant height, number of leaves and tuber diameter, where the best combination was found in the application of Kasgot as much as 400 grams/polybag + PGPR 30 ml/litre of water. Lastly the best dosage Kasgot was in the treatment of 400 grams/polybag and the best PGPR concentration was 40 ml/litre of water. Keywords: Black Soldier Fly (BSF) Kasgot, Plant Growth Promoting Rhizobacteria (PGPR) Bamboo Root, Canopy Variety.